A study on role of chest X-rays in children above 5 years admitted with asthma exacerbation - Sujonitha John; M D Jaidev; Habeeb Ullah Khan; Pavan Hegde (Wolters Kluwer Medknow Publications, 2018)
Context: Asthma is a heterogeneous disease characterized by chronic airway inflammation that causes airway hyperresponsiveness. The diagnosis of asthma is mainly clinical, and chest X-rays are not required for the diagnosis or grading of severity of disease. Aim: The aim of this study is to look at the frequency of abnormalities and the pattern of abnormalities in chest X-rays done in children above 5 years admitted with acute asthma and to analyze if chest X-ray reports altered the ongoing treatment plan. Settings and Design: It was a retrospective study done in a tertiary care hospital. Methods: Data were collected from case records of children above 5 years admitted with acute asthma between November 2014 and October 2017. Statistical Analysis: The statistical analysis was done using Chi-square and Fisher's exact test. Results: A total of 114 children were included in the study, and 84 (74%) had chest X-rays performed of which 88% were normal. Nineteen (22.6%) complied with standard guidelines, and the reason for performing chest X-rays in these children was the presence of focal clinical chest signs. When there were focal clinical findings, the possibility that chest X-ray would be abnormal was 47.37%. When there were no focal clinical findings, the possibility that chest X-ray would be normal was 98.46%. The sensitivity of chest X-rays with clinical correlation was 90% and specificity was 86.48%. Hence, routine chest X-rays in the standard treatment of acute asthma are not necessary, especially when there are no focal clinical findings. Conclusion: Chest X-ray is not required in the management of acute asthma in children above 5 years responding to standard treatment. Chest X-rays should be ordered in the management of acute asthma only when indicated, thereby reducing unnecessary exposure to radiation.